2010
DOI: 10.1121/1.3298451
|View full text |Cite
|
Sign up to set email alerts
|

The use of interaural time and level difference cues by bilateral cochlear implant users

Abstract: Abstract:While considerable evidence suggests that bilateral cochlear implant (CI) users' sound localization abilities rely primarily on interaural level difference (ILD) cues, and only secondarily, if at all, on interaural time difference (ITD) cues, this evidence has largely been indirect. This study used head-related transfer functions (HRTFs) to independently manipulate ITD and ILD cues and directly measure their contribution to bilateral CI users' localization abilities. The results revealed a strong reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 8 publications
4
106
0
1
Order By: Relevance
“…This may suggest that the measure of binaural fusion depends on the task, and the interpretation of the percentage of fused responses is complicated. An important caveat is that, unlike the NH subjects in the current study, CI users have considerable deficits in terms of interaural time difference (ITD) sensitivity when using their clinical processors (Aronoff et al, 2010;Seeber and Fastl, 2008). The availability of ITD cues was minimally altered in this experiment, particularly since the HRTFs were applied after vocoding, better preserving fine structure ITD cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest that the measure of binaural fusion depends on the task, and the interpretation of the percentage of fused responses is complicated. An important caveat is that, unlike the NH subjects in the current study, CI users have considerable deficits in terms of interaural time difference (ITD) sensitivity when using their clinical processors (Aronoff et al, 2010;Seeber and Fastl, 2008). The availability of ITD cues was minimally altered in this experiment, particularly since the HRTFs were applied after vocoding, better preserving fine structure ITD cues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nopp et al (2004), Aronoff et al (2010), and Majdak et al (2011) found RMS errors of 29…”
Section: Discussionmentioning
confidence: 99%
“…However, because so little is known about ILD sensitivity with any of these stimuli, further research is required. In particular, because CIs transmit ILDs better than ITDs (van Hoesel, 2004;Aronoff et al, 2010;Litovsky et al, 2012) children with CIs may show better ILD than ITD sensitivity, in which case future research should explore the importance of envelope shape for ILD sensitivity. Another possibility is that the difference between GET and transposed for ILD stimuli was due to an order effect because GET was always tested before the transposed tone stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In Grantham et al (2007), CI users showed a significant increase in free-field localization error for low-pass filtered noise compared to wide-band noise but no difference in performance for highpass noise compared to wide-band noise, suggesting that localization of noise bursts is primarily based on highfrequency ILDs and not low-frequency ITDs. Aronoff et al (2010) used VAS techniques to determine the relative contribution of ITD and ILD to sound localization in CI users. By modifying head-related transfer functions to present stimuli that varied in ITDs or ILDs separately, they found that when ITDs were varied and ILDs held constant, sound localization performance was significantly poorer compared to free-field localization.…”
Section: Introductionmentioning
confidence: 99%